Endovascular Therapy for Basilar Arterial Trunk Aneurysms - Wang, Yiheng; Xu, Kan; Song, Jia; Yu, Jinlu (Frontiers in Neurology, 2021)
Background: Although aneurysms rarely occur in the basilar artery (BA) trunk, the majority of those that do are dissection aneurysms. Currently, the mainstream therapy for BA trunk aneurysms is endovascular therapy (EVT), which mainly includes single coiling or conventional low-metal-coverage stent-assisted EVT, but the efficacy remains to be evaluated. Methods: A retrospective study was performed for the patients who were admitted to our institution for BA trunk aneurysms and underwent EVT. A total of 28 patients were collected in this study. Results: The patients were aged 23 to 71 years (53.7±11.5 years on average); nine were female (32.1%, 9/28), and 19 were male (67.9%, 19/28). The patients were given single coiling or conventional low-metal-coverage stent-assisted EVT. Among the 28 patients, 10 (35.7%, 10/28) developed complications, 90% (9/10) of which were ischemic and 10% (1/10) were hemorrhagic. Among the 28 patients, 5 (17.9%, 5/28) died. The surviving 23 patients (82.1%, 23/28) recovered well. Conclusions: This study found that for BA trunk aneurysms, single coiling or conventional low-metal-coverage stent-assisted EVT still had some risks. The risks are mainly from brainstem ischemia. Therefore, the perforators of the BA trunk must be carefully evaluated and prevented from receiving damage from the EVT procedure. This study also shows that 82.1% of patients recovered well. Therefore, EVT can result in an acceptable prognosis.